Genomic Study of Chromosomally and Plasmid-Mediated Multidrug Resistance and Virulence Determinants in Klebsiella Pneumoniae Isolates Obtained from a Tertiary Hospital in Al-Kharj, KSA - Ehssan Moglad; Nuor Alanazi; Hisham N. Altayb (MDPI AG, 2022)
Klebsiella pneumoniae is an emergent pathogen causing respiratory tract, bloodstream, and urinary tract infections in humans. This study defines the genomic sequence data, genotypic and phenotypic characterization of K. pneumoniae clinically isolated from Al-Kharj, KSA. Whole-genome analysis of four K. pneumoniae strains was performed, including de novo assembly, functional annotation, whole-genome-phylogenetic analysis, antibiotic-resistant gene identification, prophage regions, virulent factor, and pan-genome analysis. The results showed that K6 and K7 strains were MDR and ESBL producers, K16 was an ESBL producer, and K8 was sensitive to all tested drugs except ampicillin. K6 and K7 were identified with sequence type (ST) 23, while K16 and K8 were identified with STs 353 and 592, respectively. K6 and K7 were identified with the K1 (wzi1 genotype) capsule and O1 serotype, while K8 was identified with the K57 (wzi206 genotype) capsule and O3b. K6 isolates harbored 10 antimicrobial resistance genes (ARGs) associated with four different plasmids; the chloramphenicol acetyltransferase (catB3), blaOXA-1 and aac(6')-Ib-cr genes were detected in plasmid pB-8922_OXA-48. K6 and K7 also carried a similar gene cassette in plasmid pC1K6P0122-2; the gene cassettes were the trimethoprim-resistant gene (dfrA14), integron integrase (IntI1), insertion sequence (IS1), transposase protein, and replication initiation protein (RepE). Two hypervirulent plasmids were reported in isolates K6 and K7 that carried synthesis genes (iucA, iucB, iucC, iucD, and iutA) and iron siderophore genes (iroB, iroC, iroD, and iroN). The presence of these plasmids in high-risk clones suggests their dissemination in our region, which represents a serious health problem.